Gait Alterations in Femoroacetabular Impingement Syndrome Differ by Sex - Lewis, Cara L. (J Orthop Sports Phys Ther, 2018)
STUDY DESIGN: Laboratory study, case-control design. OBJECTIVES: Investigate if individuals with femoroacetabular impingement (FAI) syndrome have different hip and pelvic motion during gait, at their preferred speed and a prescribed speed, compared to individuals of the same sex without pain. BACKGROUND: FAI syndrome may affect gait kinematics differently between males and females. METHODS: Eleven males and 10 females with FAI syndrome and 19 males and 22 females without hip pain participated. Groups were not different in age, body mass index, or activity score. Kinematic data for all participants were collected while walking at a preferred speed and at 1.25 m/s. For each sex and walking speed, linear regression analyses examined the effect of group and the interaction of group-by-limb. RESULTS: At both speeds, males with FAI syndrome walked with more than 6° less peak hip extension (P ≤ .018), 5° greater anterior pelvic tilt (P ≤ .020), and 5° less posterior pelvic tilt (P ≤ .018) compared to males without hip pain. Females with FAI syndrome walked with 2° less hip extension (P ≤ .012) and at least 3° more hip adduction (P < .001) in the more painful hip than in the less painful hip at both speeds. CONCLUSION: Males and females with FAI syndrome have different gait alterations when compared to a same sex comparison group. In males, differences were between groups. In females with FAI syndrome, differences were between the more painful and less painful limb.